Efecto de la conductividad eléctrica a partir de la salinidad y sólidos disueltos en los procesos biológicos de nitrificación y desnitrificación para la remoción de compuestos nitrogenados en aguas residuales domésticas (2023)
Compliance with Sustainable Development Goals (SDGs) number six "clean water and sanitation", twelve "responsible production and consumption" and fourteen "Conserve and sustainably use the oceans, seas and marine resources", are known to be a challenge. Likewise, water pollution gradually decreases economic evolution and brings with it alterations to the environment and health. According to DANE data, in 2020 there was an increase in wastewater of 0.8% compared to 2019, so that the treatment of these also grew by 1.4%, although nitrogen is a component that is increasing due to human activity. Therefore, this degree project studies the possible effects generated by concentrations of electrical conductivity from total dissolved solids (TDS) and salinity, in the removal of nitrates in the biological treatments of nitrification and denitrification of domestic wastewater. Initially, an analysis of existing information and studies was carried out, identifying the possible impacts of this parameter on the efficiency of the treatment system, in such a way that they could be compared with a study in a full-scale PTARD; in which electrical conductivity ranges from 1020 μS/cm to 650 μS/cm, salinity less than 0.29 ppt and total dissolved solids (TDS) 670 mg/L to 450 mg/L were determined, with which a greater efficiency was obtained in the removal of nitrates (NO3), promoting the evaluation of these parameters in the designs of biological treatment systems of domestic wastewater, for the optimal nitrification and denitrification process with the concentrations and parameters that help a high performance of the treatment in domestic wastewater